Une occupation rurale du second âge du Fer et du Haut-Empire sur le site de l’aérodrome à Chartres (Eure-et-Loir) - Bruno Lecomte; Jonathan Simon (Revue Archéologique du Centre de la France)
A rural settlement dating from the Second Iron Age and the Roman period has been unearthed on the airfield site in Chartres.During the first phase of its occupation, dated to the Final Hallstatt or Early La Tène period, it comprised just a few structures, including a probable enclosure. The organisation of the site is difficult to determine, given the paucity of remains unearthed. The presence of a small cellar indicates relatively long-term occupation of this small settlement, the total area of which is unknown.The site was occupied again from La Tène D2a onwards. This rural occupation was marked by a trapezoidal ditched enclosure with an internal partition. The two spaces thus defined are marked by the presence of several buildings, one of which may be associated with a smithy. The morphology of the enclosure attests to a livestock-raising activity, the characteristics of which can be seen in the fauna discarded, mainly from the enclosure ditches.Lastly, a final enclosure dating from the Early Roman period succeeded the earlier agricultural settlement abandoned in the La Tène D2b or early Augustan period. This enclosed occupation was only partially visible. The few structures identified, dated to the early 1st century AD, indicate the proximity of a settlement located outside the excavation area.